EFEKTIVITAS TRANSFER PUSAT TERHADAP PEREKONOMIAN PROVINSI LAMPUNG - Hery Budi Setyawan (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2013)
Implementation of fiscal decentralization has implications on the central transfer through the General Alloction Funds (DAU), special allocation Funds (DAK) and revenue-sharing Funds (DBH). The central transfer becomes an important factor in the locsl development dynamics which will bring impact on the economic performance . This article aims identify the extent of central transfer and macro variables effectiveness on the economy of Lampung Province. Lampung Province was chosen as pbject research, considering that it play an effective role in connecting sumatra with java, Analysis on data form panel is used for ten regencies/cities between 2003 and 2009 throught three phases: pooled least square (PLS) fixed effect model (FEM) and random effect model (REM). REM model is the best available for describing the data. Result of estimations shows that DAU and investment are statistically significant in influencing positive economic growth in Lampung Provience. On the other hand, DBH has negative impact on the economy, albeit the magnitude of all three variables is minuscule compared to the entire economy. This indicates ineffectiveness in using central transfer to accelerate growth due to misalocation of budget for consumptive activies compared to investment, which in turn renders capital inefficientand ICOR elevated.